2022
DOI: 10.3389/fpls.2022.1013184
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil bacterial community and functions by substituting chemical fertilizer with biogas slurry in an apple orchard

Abstract: Growing concerns about the negative environmental effects of excessive chemical fertilizer input in fruit production have resulted in many attempts looking for adequate substitution. Biogas slurry as a representative organic fertilizer has the potential to replace chemical fertilizer for improvement of sustainability. However, it is still poorly known how biogas slurry applications may affect the composition of soil microbiome. Here, we investigated different substitution rates of chemical fertilizer with biog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Many studies have shown a strong correlation between soil chemical properties, soil bacterial communities, and fruit yield and quality ( Liu et al, 2020 ; Wang Z. H. et al, 2022 ; Zhang et al, 2022b ). The same results were found in our correlation analysis, in which many soil bacteria were significantly positively correlated with soil chemical properties and peach yield and quality ( Figure 4A ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown a strong correlation between soil chemical properties, soil bacterial communities, and fruit yield and quality ( Liu et al, 2020 ; Wang Z. H. et al, 2022 ; Zhang et al, 2022b ). The same results were found in our correlation analysis, in which many soil bacteria were significantly positively correlated with soil chemical properties and peach yield and quality ( Figure 4A ).…”
Section: Discussionmentioning
confidence: 99%
“…Digested slurry is rich in nutrient elements, including nitrogen, phosphorus, potassium, zinc, iron, as well as trace elements and organic matter (Li et al 2017b;Ke et al 2022). These substances can be used by plants for growth and development, the application can be quick and efficient, and the nutrients can easily be absorbed (Cao et al 2016;Liu et al 2022;Zhang et al 2022). Also, the nutrients have a high utilization efficiency (Wu et al 2013).…”
Section: Introductionmentioning
confidence: 99%